Adaptive hybrid partitioning for OLAP query processing in a database cluster. (29th December 2008) - Furtado, Camille; Lima, Alexandre A.B.; Pacitti, Esther; Valduriez, Patrick; , Marta Mattoso
We consider the use of a database cluster for high-performance support of Online Analytical Processing (OLAP) applications. OLAP intra-query parallelism can be obtained by partitioning the database tables across cluster nodes. We propose to combine physical and virtual partitioning into a partitioning scheme called Adaptive Hybrid Partitioning (AHP). AHP requires less disk space while allowing for load balancing. We developed a prototype for OLAP parallel query processing in database clusters using AHP. Our experiments on a 32-node database cluster using the TPC-H benchmark demonstrate linear and super-linear speedup. Thus, AHP can reduce significantly the execution time of typical OLAP queries.